Preferences for HIV testing services among young people in Nigeria - Nwaozuru, Ucheoma (BMC Health Serv Res, 2019)
BACKGROUND: Despite high HIV incidence rates among young people in Nigeria, less than 24% of this population have ever tested for HIV. These low HIV testing rates suggest that current testing services may not align with their testing preferences. To address this gap, the objective of this study was to assess preferences for HIV testing options among young people in Nigeria. METHODS: We conducted a cross-sectional study using survey to assess preferences for HIV testing options among 113 youth aged 14–24 years residing in Nigeria. The survey included a series of hypothetical HIV testing options, comprised of six characteristics centered around HIV testing service (i.e. location of testing, test administrator, mode of pre-test, mode of post-test counseling, type of HIV test, and cost of HIV test). For each characteristic, participants were asked to select one of the options that they prefer or indicate none of the above. A descriptive analysis of the preferences made by participants was conducted, summarizing proportions of participants who selected different options for HIV testing. RESULTS: The mean age of study participants was 19.5 years old (SD = 2.7). Most youth (73, 64.6%) had at least a secondary school degree. There was pronounced heterogeneity in HIV testing preferences among young people. Although most youth preferred free HIV testing, 14 (16.7%) reported preferring paying a small amount compared to free testing. More youth preferred blood-based HIV self-testing 39(48.8%) compared to facility-based HIV testing and oral HIV self-testing. CONCLUSIONS: Our finding suggest that young people have a range of HIV testing preferences in Nigeria. This suggests that a “one-size-fits-all” approach to delivering services to youth may be challenging in this context. HIV testing services can be optimized to reach young people if a variety options are provided to meet their unique preferences.